2p24.2 (rs7552) is a susceptibility locus for nonsyndromic cleft lip with or without cleft palate in the Brazilian population. Issue 6 (25th March 2018) - Machado, R.A.; Nogueira, E.N.; Martelli‐Júnior, H.; Reis, S.R.; Persuhn, D.C.; Coletta, R.D.
Abstract : The population of Brazil is highly admixed, with each individual showing variable levels of Amerindian, European and African ancestry, which may interfere in the genetic susceptibility of known risk loci to nonsyndromic cleft lip with or without cleft palate (NSCL±P). Here, we investigated 5 reported genome‐wide loci for NSCL±P in an ancestry‐structured case‐control study containing 1697 Brazilian participants (831 NSCL±P and 866 healthy controls). SNPs rs7552 in 2q24.2, rs8049367 in 16p13.3, rs1880646, rs7406226, rs9891446 in 17p13, rs1588366 in 17q23.2 and rs73039426 in 19q13.11 were genotyped using TaqMan allelic discrimination assays and genomic ancestry was estimated using a panel of 40 biallelic short insertion/deletion polymorphic markers informative of the Brazilian population. Logistic regression analysis of the single‐markers revealed rs7552 in 2p24.2 as a susceptibility risk marker for NSCL±P, yielding an odds ratio (OR) of 1.71 (95% confidence interval (CI): 1.31‐2.24, P = 9 × 10 −6 ) in the homozygous state. Several SNP‐SNP interactions containing rs7552 reached significance after adjustment for multiple tests (both Bonferroni assumption and 1000 permutation test), with the most significant interaction involving the 3‐loci among rs7552, rs9891446 and rs73039426 ( P = 6.1 × 10 −9 and p 1000 permutation = 0.001). Our study is the first to support the association of rs7552 in 2p24.2 with NSCL±P in the highly admixed Brazilian population. Abstract :